Strategi Sultan Thaha Syaifuddin dalam Melawan Penetrasi Belanda di Kesultanan Jambi (1855-1904) - Rosyadi, Ratih Ummi; Pradjoko, Didik (Universitas Batanghari Jambi, 2023)
This research discusses the resistance strategy of Sultan Thaha against the Dutch in 1855-1904 through guerrilla efforts so that it became one of the people's resistances which took quite a long time before Jambi was successfully conquered by the Dutch in 1906. Since the political direction of Dutch imperialism changed in the archipelago after the signing of the Treaty of London in 1824, British intervention resulted in the Dutch having to review local authority contracts to guarantee their sovereignty. Sultan Thaha as the Sultan of the Jambi Kingdom tried to break the contractual ties with the Dutch by physically and diplomatically resisting the hegemony of the Dutch power which increasingly urged Jambi to remain submissive. This became the topic of the writer's problem about the efforts and strategies launched by Sultan Thaha in defending Jambi amid the pressure that the Dutch continued to make. The author tries to reconstruct using historical methods to reveal how the steps taken by Sultan Thaha in seeking people's support and the strategies used to defend Jambi from Dutch penetration.